M6A-Mediated Upregulation of LINC00106 Promotes Stemness and Metastasis Properties of Hepatocellular Carcinoma via Sponging Let7f - Liang, Wenjin; Wang, Yan; Zhang, Qinyu; Gao, Min; Zhou, Haizhou; Wang, Zhenran (Frontiers in Cell and Developmental Biology, 2021)
Background: Hepatocellular carcinoma (HCC) cells exhibit the stemness property, which makes the patient with HCC prone to tumor recurrence and metastasis. Despite the prominent regulatory role of long non-coding RNAs (lncRNAs) in tumor stemness, the roles and molecular mechanisms of LINC00106 in HCC are poorly understood. Methods: LINC00106, let7f and periostin expression levels in tissue specimens and cell lines were assessed through qRT-PCR and immunohistochemistry (IHC). Various in vivo and in vitro assays, namely sphere/colony formation, proportion of side population cells (SP%), invasion, migration, western blot, and murine xenograft model were employed for assessing the stemness and metastatic properties of HCC cells. Luciferase reporter assays, RNA-seq, RNA pull-down, RNA immunoprecipitation (RIP) were conducted to clarificate the target gene and analyze the underlying mechanisms. Results: LINC00106 was prominently upregulated in tissues and cell lines of HCC. Patients having a high LINC00106 level exhibited a poor outcome. Under in vivo and in vitro conditions, the stemness and metastatic properties of HCC cells were augmented by LINC00106. Additionally, LINC00106 was found to sponge let7f to upregulate periostin, which lead to the activation of periostin-associated PI3K-AKT signaling pathway. Moreover, m6A methylation was found to cause LINC00106 upregulation while maintaining LINC00106 RNA transcript stability. Conclusion: m6A methylation triggers the upregulation of LINC00106, which promotes the stemness and metastasis properties in HCC cells by sponging let7f, thereby resulting in periostin activation. The findings indicate the potential of LINC00106 as a diagnostic marker and therapeutic target for HCC.